Inclusive Education : Contributions from an Experience in Uruguay - World Bank (World Bank, Washington, DC, 2018)
This report describes an experience, developed jointly by the Uruguayan National Department of Public Education (ANEP) and the World Bank, of the implementation of an Inclusive Education component. The goal is to demonstrate a concrete example of what countries can do to implement such inclusive education in practice, within the framework of strategies proposed by the “Education for All” initiative and the Millennium Development Goals (MDGs).This document does not attempt to provide either details of the conceptual framework or political arguments for setting the international guidelines of inclusive education programs, but rather responds to the demand for practical examples that illustrate an operational strategy. One of the promising characteristics of the Uruguayan experience with the implementation of the Inclusive Education component was that it did not require additional programs or resources; rather, the process was incorporated as a new tool within an overall strategy for improving the quality of education in the country.Although the fact that the component has only recently been implemented (2003) prevents an exhaustive study of its results and impact thus far, publicizing the experience internationally is justifieddue to the need for documentation of actual experiences developed on a national scale. It is hoped that this will allow the public to envisage models for the implementation of inclusive education.